Retail service quality as a base in purchasing decision - Sokolov-Mladenović Svetlana; Ćuzović Sreten (Marketing (Beograd. 1991), 2015)
Retail is a service activity, and services are something that makes the retail companies differ from production companies. Retailers are trying to differentiate the 'package' offer, build customer loyalty and make their position through the provision of high service quality. In addition, the services provided can be varied, such as exterior and interior design of retail stores, preparation of goods for sale, appearance and behavior of sales personnel, culture of communication with customers, and services provided after the sales process. Consumers require the service quality when making purchasing decision. For retail companies and retail stores it is important to continuously monitor the level of service quality. In order to measure the service quality, the method that found its application in the theory and practice is SERVQUAL. This model was created as a combination of theoretical and practical research and it looks at the quality of service as the content of the following dimensions: tangibles, reliability, sensitivity, security and empathy. As such, it is a function of the difference between perceptions and expectations (Q = P-E) and is widely accepted to measure the service quality in traditional retail stores, public sector, higher education, real estate, hospitals, courts and so on. In addition, this model is widely used to measure service quality in e-retailing, e-banking, e-selling of travel packages and other services provided by electronic means. The main assumption is that services are a key factor in making purchasing decision. The aim of this paper is to, through theoretical and practical research with special emphasis on SERVQUAL method, test the initial hypothesis and recognize the level of service quality in retail chains in Southeast Serbia.